REDISCOVERY OF Campanacella hamiltonella (WESTWOOD, 1867) (NEUROPTERA: MANTISPIDAE) FROM INDIA AFTER 155 YEARS - KUMAR, RAHUL; SHARMA, AJAY KUMAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
A rare neuropteran species Campanacella hamiltonella (Westwood, 1867) (family Mantispidae, sub-family Mantispinae) has been reported from the Chotanagpur Plateau, India for the first time. It is also the first record of this species from India after 1867. Morphological descriptions of the habitus are provided with digital illustrations. Mimetic features of this species are also discussed. A potter wasp species Phimenes flavopictum Blanchard, 1845 has also been reported from the same habitat whose abdominal coluoration is mimicked by C. hamiltonella. Discovery of C. hamiltonella from Chotanagpur Plateau suggests its extended geographical range in India which was earlier known to be restricted to Arunachal Pradesh only.